2020
DOI: 10.1126/sciadv.aaz3112
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastable lithium metal anode enabled by designed metal fluoride spansules

Abstract: The lithium metal anode (LMA) is considered as a promising star for next-generation high-energy density batteries but is still hampered by the severe growth of uncontrollable lithium dendrites. Here, we design “spansules” made of NaMg(Mn)F3@C core@shell microstructures as the matrix for the LMA, which can offer a long-lasting release of functional ions into the electrolyte. By the assistance of cryogenic transmission electron microscopy, we reveal that an in situ–formed metal layer and a unique LiF-involved bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(122 citation statements)
references
References 57 publications
3
119
0
Order By: Relevance
“…In this context, Yuan et al also reported that certain metal species (e. g., metal fluorides) can have a significant impact on the uniformity of Li metal deposition and dissolution in Li metal cells. [63] The different impacts of various dissolved TMs on the morphology of Li metal deposits on Li metal has been also reported by Betz et al [40] Overall, these studies give a first indication of the significant impact of TMs on the homogeneity and uniformity of Li metal deposits, however, further studies are needed to clearly understand the impact of individual TMs and specific TM species.…”
Section: Mechanistic Elucidation Of High-voltage Induced Cell Failuresupporting
confidence: 59%
See 1 more Smart Citation
“…In this context, Yuan et al also reported that certain metal species (e. g., metal fluorides) can have a significant impact on the uniformity of Li metal deposition and dissolution in Li metal cells. [63] The different impacts of various dissolved TMs on the morphology of Li metal deposits on Li metal has been also reported by Betz et al [40] Overall, these studies give a first indication of the significant impact of TMs on the homogeneity and uniformity of Li metal deposits, however, further studies are needed to clearly understand the impact of individual TMs and specific TM species.…”
Section: Mechanistic Elucidation Of High-voltage Induced Cell Failuresupporting
confidence: 59%
“…In this context, Yuan et al. also reported that certain metal species (e. g., metal fluorides) can have a significant impact on the uniformity of Li metal deposition and dissolution in Li metal cells [63] . The different impacts of various dissolved TMs on the morphology of Li metal deposits on Li metal has been also reported by Betz et al [40] .…”
Section: Resultsmentioning
confidence: 78%
“…[1,2] Nevertheless, the large-scale application of LMBs is inherently inhibited by the uncontrollable growth of Li dendrite on Li anode. [3,4] The typical issue is addressed through various strategies, for example, the interfacial SEI engineering, [5,6] stable hosts construction, [7,8] and solid electrolyte design. [9,10] Among the strategies, the solid state electrolytes, particularly the solid polymer electrolytes (SPEs) for LMBs, have gained tremendous interest for many decades.…”
Section: Doi: 101002/adma202000223mentioning
confidence: 99%
“…However, modern day LIBs use liquid-based electrolytes that enable propagation of lithium dendrites, and so pose significant safety concerns with the use of a Li metal anode 3 . Despite intensive research to prevent dendritic growth [4][5][6][7][8][9][10] , a practical solution to eliminate this issue remains elusive. Furthermore, these electrolytes are flammable, toxic, non-renewable and often have a limited electrochemical window (preventing use of high V cathode materials), hence they are not ideal for the high energy demands of modern-day society 2,[11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%